Het islamdebat – laveren tussen uitersten - de Ruiter, Jan Jaap (Religie & Samenleving, 2015)
In this essay the author treats the debate in the Netherlands about Islam, the Arab Spring and the ideology of the populist Party For Freedom. In the treatment of these subjects he goes as well into his vicissitudes as opinion maker.